Abstracts - Jensen, Mikkel Storm; Friis, Karsten; Jacobsen, Jeppe Teglskov; Willers, Johann Ole; Lentz, Lene Wacher; Pedersen, Jens Myrup; Olesen, Finn; Erbas, Mina; Suenson, Emil Lobe Wellington; Larsen, Bøje (Økonomi & Politik, 2020)
Abstracts of each article